Fungi Associated with Postharvest Diseases of Sweet Potato Storage Roots and In Vitro Antagonistic Assay of Trichoderma harzianum against the Diseases - Narayan Chandra Paul; Soyoon Park; Haifeng Liu; Ju Gyeong Lee; Gui Hwan Han; Hyunsook Kim; Hyunkyu Sang (Journal of Fungi, 2021)
Sweet potato is the 11th most important food crop in the world and an excellent source of nutrition. Postharvest diseases were monitored in sweet potato storage roots collected from the local markets in Korea during 2021. Several diseases including Fusarium surface and root rot, charcoal rot, dry rot, and soft rot were observed in the postharvest sweet potatoes. A total of 68 fungal isolates were obtained from the diseased samples, and the isolates were grouped into 8 different fungal colony types. Based on multilocus phylogeny and morphological analysis of 17 representative isolates, the isolates were identified as Fusarium oxysporum, F. ipomoeae, F. solani, Penicillium citrinum, P. rotoruae, Aspergillus wentii, Mucor variicolumellatus (Mu. circinelloides species complex), and Macrophomina phaseolina. F. oxysporum was the predominant pathogen as this is the most common pathogen of sweet potato storage roots causing the surface rot disease, and M. phaseolina caused the most severe disease among the pathogens. Dual culture antagonistic assays were evaluated using Trichoderma harzianum strains CMML20–26 and CMML20–27. The results revealed that the two strains showed strong antifungal activity in different ranges against all tested pathogens. This study provides an understanding of diverse postharvest diseases in sweet potatoes and suggests potential biocontrol agents to manage the diseases. In addition, this is the first report of sweet potato storage root rot diseases caused by A. wentii, and P. rotoruae worldwide.